Pengetahuan dan Sikap Calon Guru Biologi pada Kesehatan Reproduksi - Herlin Andayani; Lukman Aprizal; bambang Hariyadi (Universitas Jambi, 2012)
Reproductive health is a major problem that occurs in Indonesian adolescents. The problem is caused by some factors, including free sex that could induce reproductive organ diseases such as cervical cancer, ovarian cancer, vulvar cancer, uterine cancer, prostate cancer and sexually transmitted diseases. Incidence of various reproductive health problems is caused by a lack of knowledge about reproductive health. This issue needs to get attention from various parties, including teachers. However, some teachers are less understood about how to deliver reproductive health materials properly. This study aims to determine knowledge and attitudes of teacher candidates about reproductive biology. This study is a descriptive analytic study. The subjects were students of biology education at Jambi University who are in 5th and 7th semesters of academic year 2011/2012 (174 students). The data was collected using tests and questionnaires. The results show that knowledge of the biology teacher candidates about the reproductive health is categorized as low (43​​%). The attitude of biology teacher candidates about reproductive biology is classified as positive (64%). The formation of attitudes toward reproductive health is influenced by several factors including knowledge, experience, guidance from parents, social environment, mass media, cultural, and social institutions.